Revisiting Supplier Compliance with MNC Codes of Conduct: Recoupling Policy and Practice at Chinese Toy Suppliers - Egels-Zandén, Niklas (2014)
Does private regulation of workers’ rights in global value chains improve working conditions on the factory floor? Drawing on one of the first systematic longitudinal studies of supplier compliance with multinational corporation (MNC) codes of conduct, this paper finds—in contrast to previous research—substantial improvements over time. While in 2004, the four examined Chinese toy suppliers violated most of the evaluated code of conduct criteria and consciously decoupled the code of conduct policy from actual practices, by 2009 they had recoupled policy and practice and complied with nearly all examined criteria (except working hours). The paper contributes to the private regulation literature by challenging previous research claims, identifying factors that could make private regulation effective, and outlining a research method for empirically studying the effects of codes of conduct over time. The paper also contributes to new institutional theory by discussing how recoupling could be influenced by two factors not identified in previous research: (i) trusting relationships between the organization and the stakeholder exerting pressure and (ii) factors unrelated to main external pressures leading to “accidental” recoupling.
Keywords: workers’ rights; Toy industry; Supplier relationships; Recoupling; Private regulation; New institutional theory; labour practice; Decoupling; codes of conduct; China